Hydrocarbon conversion process - SCHRADER; CHARLES H; LIONETTI; THOMAS A (1983)
A process for the production of highly aromatic petroleum fractions from various petroleum feedstocks suitable for catalytic cracking in a fluidized catalytic cracking unit wherein heavy gas oil from a first fluidized catalytic cracking unit is subjected to further catalytic cracking in a separate fluid catalytic cracking unit at temperatures in the range of 565 DEG to 650 DEG C. producing light olefins and a heavy gas oil consisting of essentially aromatic components suitable for the production of needle coke, and the method of producing needle coke from various hydrocarbon cracking stocks.